Learning Tableau 2019 tools for business intelligence, data prep, and visual analytics - Milligan, Joshua N. (Packt Publishing, 2019)
Tableau 2019 is the gold standard of business intelligence and visual analytics. It empowers rapid data visualization and advanced analytics with charts, graphs, dashboards, and powerful analytic tools. This book lays a strong foundation of the Tableau paradigm and builds to advanced topics, including Tableau Prep, to make you an expert.